"The Best Damn Representation of Islam:" Muslims, Gender, Social Media, and Islamophobia in the United States. Issue 1 (31st December 2020) - Eckert, Stine; Wallace, Sydney O'Shay; Metzger-Riftkin, Jade; Kolhoff, Sean
Abstract: Islamophobia reached new heights during the 2016 United States presidential election. We applied the theory of intersectionality to 15 in-depth focus group interviews conducted in gender-separated groups with 61 Muslim participants (41 women, 20 men) in South East Michigan between October 2016 and April 2017 to understand the role of gender in their responses regarding Islamophobia during the 2016 United States presidential election and Trump's first hundred days in office as president. Both, Muslim women and Muslim men, labored to educate others about Islam online, but Muslim women emphasized their efforts to act as exemplars online of what it means to be Muslim in America more frequently and more strongly than men. Muslim women and men often used ignoring and contextualization as coping mechanisms as the number of Islamophobic messages online was perceived as overwhelming. The high amount and ubiquity of Islamophobic messages online has lead to a sense of futility and high levels of stress among young Muslims in South East Michigan, particularly for Muslim women.